Mycotoxin contamination of foods in Africa: antinutritional factors - Cardwell, K.F. (SAGE Publications, 2000)
Mycotoxins are regulated in foods and feeds because of carcinogenic (aflatoxin), immunotoxic (deoxynivalenol), or environmental estrogenic (zearalenone) properties. In addition to having tumorigenic properties, many mycotoxins are antinutritional factors that cause unthrifty growth and immune suppression in young animals. In the developed world, human exposure, and particularly exposure of children, to dietary mycotoxins is virtually nonexistent because of regulatory standards. In developing countries, monitoring and enforcement of standards is rare, and mycotoxin-susceptible foods are often the primary staples in rather undiversified diets. In sub-Saharan Africa, people are exposed to unsafe levels of various mycotoxins, often in mixtures, and the consequences in terms of public health burden have been ignored. This paper presents information on the health effects that have been attributed to mycotoxin exposure from the medical research literature and data on existing mycotoxin levels in maize in West and Central Africa. The International Institute of Tropical Agriculture (IITA), in its Maize Integrated Pest Management Project, has recognized mycotoxins as one of the most important constraints to the goal of improving human health and well-being through agriculture. An overview of various research and development activities at the Institute is given.